Pemberdayaan Potensi Masyarakat Melalui Pengembangan Perdagangan, Pendidikan, Sosial, dan Lingkungan Desa Gedangan Kecamatan Grogol Kabupaten Sukoharjo - Puspanda Hatta; Agus Budiarto; Imam Prasetyo; Putri Karimah; Abdillah Yusron (FKIP Universitas Sebelas Maret, 2021)
Gedangan is a village located in Grogol District, Sukoharjo Regency, Central Java. In 2021, Gedangan Village will become one of the partners of the Sebelas Maret University Student Community Services Program (KKN). In this village, KKN activities were carried out using a hybrid system due to the pandemic. KKN is carried out through online and offline activities with the theme of empowering community potential through counselling in the fields of animal husbandry, education, social and creative industries. The work programs that have been implemented are